PERSISTENSI LABA BERDASARKAN PERBEDAAN BUKU PAJAK, ARUS KAS OPERASI, DAN UKURAN PERUSAHAAN (Jurnal Riset Akuntansi, 2022)
This study analyzed the effect of book-tax differences (BTD), operating cash flows (OCF), and firm size on earnings persistence. This study also used the firm's size as a moderating variable to maximize or minimalize the effect of BTD and OCF on earnings persistence. This study employed the balanced panel data from 22 companies in the consumer goods industry from 2015 to 2019 with 110 observations. This study employed the principal component analysis (PCA) of permanent and temporary differences to measure BTD. By using the random effect regression model, this study found that BTD and the firm's size did not affect earnings persistence. On the other hand, this study found that OCF positively affects earnings persistence. In addition, the firm's size has a positive moderating role in the effect of OCF on earnings persistence. However, the firm's size was not proven to have a moderating role in the effect of BTD on earnings persistence. These results implied that the firm's OCF determines earning persistence or sustainability. Keyword : Book-tax differences, Earning Persistence, Operating Cash Flows